(untitled) (Journal of actual problems of jurisprudence, 2016)
This work focuses on the study of basic labor laws and regulations in the PRC, and in the Republic of Kazakhstan. The purpose of this study is to investigate and identify problems in the legal regulation, with the involvement of foreign experts. Economic development of our countries, in recent times is of interna- tional significance, because of the so-called agreements. Frequent use of experts from both the PRC and by RK requires some control. The lack of complete control on the one hand and meticulous control of the other The sides, but other than that and illegal migration, affects the quality of the indigenous inhabitants.